Clinical evaluation of day surgery for anal fistula excision with MRI-assisted diagnosis: a retrospective analysis of 121 cases - Zhang, Shaohua; Chen, Fangying; Wei, Yifan; Ma, Xiaolu; Lu, Haidi; Luo, Youyu; Hao, Liqiang; Lu, Jianping; Hong, Yonggang (Frontiers in Medicine, 2025)
ObjectiveThe clinical practice of anal fistula excision surgeries conducted in the day surgery unit was analyzed, and the efficacy and safety of this surgery were evaluated.MethodsThe clinical data of 121 patients with anal fistulas who underwent excision surgery at Changhai Hospital from October 2021 to April 2024 was retrospectively analyzed, including age, gender, body mass index (BMI), diagnosis, fistula characteristics (number and locations of internal and external openings), preoperative magnetic resonance imaging (MRI) of fistulas, surgical and anesthetic methods, length of hospital stay, verbal rating scale (VRS), outpatient follow-up frequency, wound healing status, rehabilitation time, postoperative complications, and patient satisfaction. Kappa statistics were employed to evaluate the value of MRI in assessing the Parks classification and the number of fistulas compared with that of intraoperative findings.ResultsAll 121 patients successfully underwent anal fistula excision or excision combined with seton placement, with no patients lost to follow-up. All patients fully recovered, achieving a cure rate of 100%. Postoperative complications were rare, with only one patient (0.3%) experiencing pruritus and no recurrence. The rate of patient satisfaction reached 96.7%. The accuracies of the Park classification and number of fistulas assessed by MRI were 95.9 and 94.2%, respectively. The Kappa values were 0.948 and 0.848, respectively.ConclusionDay surgery for anal fistula excision resulted in shorter hospital stays, lower medical costs, and fewer postoperative complications. Furthermore, MRI provided a reliable preoperative assessment of the Parks classification and the number of fistulas. Such an approach is a safe and feasible surgical treatment that deserves wider adoption.